RUSSELL TRIBUNAL ON HUMAN RIGHTS IN PSYCHIATRY & "GEIST GEGEN GENES", 30 JUNE - 2 JULY 2001, BERLIN - Parker, Ian (PINS-Psychology in Society, 2026)
The first Russell Tribunal, which was opened by Bertrand Russell and concluded by Jean-Paul Sartre, was held in 1967. It focussed on the conduct of the United States in the Vietnam War. The Bertrand Russell Peace Foundation then conducted further public tribunals on repression in Latin America, freedom of opinion in West Germany and the condition of first nation peoples in the United States. This fifth Tribunal on Human Rights in Psychiatry, then, stands in a tradition of political interrogation that mobilises people to speak out and to act. Over the two days of hearings, witnesses testified to the abuse they had suffered at the hands of the psychiatric system and expert witnesses described how people had been coerced into "treatment", sometimes with horrifying results. This was an international tribunal, with an international remit, which allowed for some unusual and necessary political alliances.